Professional Identity in Transition: Insights from Indonesian Senior High School Counselors - Agus Taufiq; Ibrahim Al Hakim; Aam Imaduddin; Eka Sakti Yudha; Dodi Suryana; Deasy Yunika Khairun; Arinnisa Cahya Nurzaman (Universitas PGRI Yogyakarta, 2026)
This study explores the multidimensional professional identity of senior high school counselors in Bandung City. Using a phenomenological approach and focus group discussions, five indicators of professional identity were identified: professional involvement, knowledge, attitudes, roles and expertise, and professional philosophy. Findings reveal that active engagement in professional organizations enhances competencies and social capital, while knowledge of the profession’s history and regulations informs ethical and effective practice. Empathy, objectivity, and relational orientation strengthen professional pride, and counselors’ roles in case management and referral highlight their adaptive and accountable function as connectors. The philosophy of guidance and counseling, grounded in preventive, strengths-based, and humanistic principles, supports holistic student development and resilience. Professional identity emerges from integrating experience, competence, ethics, and collaboration, contributing to improved counseling services and student well-being. Keywords: phenomenology, professional identity, preventive guidance, school counselors, strengths-based approach